2016
DOI: 10.1177/1461355716638686
|View full text |Cite
|
Sign up to set email alerts
|

Influences and vulnerabilities in radicalised lone-actor terrorists

Abstract: The threat to national security from terrorists acting on their own initiative is a challenge for law enforcement and intelligence agencies in the UK and elsewhere. The UK Parliament’s 2014 threat assessment noted ‘a trend towards ‘low signature’ terrorism by small, self-directed groups and lone actors’ [House of Commons Home Affairs Committee (2014) Counter-Terrorism – Seventeenth Report of Session 2013–14]. Lone actors have become a higher priority for counter-terrorism professionals (UK police, Prevent prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
0
22
2
Order By: Relevance
“…In the case of the youth workers, it has been shown that these perspectives are mainly formed from individual know-how and personal development based on individual life experiences. In practice, there is an insufficient methodological perspective on extremism for youth workers to rely on (Mattsson, 2017;Peddell et al, 2016). Therefore, implementing CVE-policy takes place on the basis of a mix of facts, norms, values and personal feelings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the youth workers, it has been shown that these perspectives are mainly formed from individual know-how and personal development based on individual life experiences. In practice, there is an insufficient methodological perspective on extremism for youth workers to rely on (Mattsson, 2017;Peddell et al, 2016). Therefore, implementing CVE-policy takes place on the basis of a mix of facts, norms, values and personal feelings.…”
Section: Resultsmentioning
confidence: 99%
“…Despite trainers' attempts to give insight into the complexity of the issue, the first studies show that in practice it is not possible to monitor and detect extremism and/or radicalisation methodically (Mattsson, 2017;Peddell et al, 2016). Knowledge about the monitoring and detection of extremism and radicalisation can therefore only be imparted to a limited extent.…”
Section: Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…This conflation, nevertheless, is pervasive. In reporting the findings of a series of interviews with Prevent practitioners, Peddell, Eyre, McManus, and Bonworth (2016) illustrate the lack of conceptual clarity surrounding the notion of 'vulnerability': "Broadly, individuals were characterised as vulnerable because of a personal characteristic that rendered them unable to resist radical discourse, or the influence of the social context in which they lived, or both. All participants viewed mental health issues as a significant factor in personal vulnerability" (p. 68).…”
Section: Introductionmentioning
confidence: 99%
“…When a front-line professional operates preventively in the area between social welfare and early-detection of violent extremism, his/her judgment is particularly unstructured and not entirely objective. Such was the outcome of the few studies about early detection that have been conducted among front-line practitioners so far (e.g., Aly, Balbi & Jacques [15]; [16][17][18][19]). This outcome seemed to stem from a lack in the necessary development of knowledge that has taken place among local security experts, in the inconsistent use of concepts such as radicalization and (violent) extremism, and in doubts about the ability to accurately assess potential risk at such a level.…”
Section: Literature Reviewmentioning
confidence: 99%